Efficacy of electroacupuncture with different frequencies in the treatment of chemotherapy-induced peripheral neuropathy: A study protocol for a randomized controlled trial - Lu, Chao; Bao, Wenlong; Deng, Dehou; Li, Rongrong; Li, Guangliang; Zou, Shanlin; Wang, Yan (Frontiers in Neurology, 2022)
Introduction: Chemotherapy-induced peripheral neuropathy (CIPN) is a common complication in cancer patients during chemotherapy. It mainly leads to severe numbness of the hands and feet and causes great pain to patients' life. Electroacupuncture(EA) is considered to be beneficial to improve peripheral neuropathy and relieve numbness of hands and feet. The purpose of this trial is to evaluate the therapeutic effect of different frequency of EA on CIPN in cancer patients. Methods and analysis: This study is a randomized controlled trial 160 eligible CIPN patients will be randomly assigned to the 2Hz EA group, 100Hz EA group, 2/100Hz EA group and control group in the ratio of 1:1:1:1. All patients in the EA treatment groups were treated with EA 3 times a week for 4 weeks and followed up for 4 weeks. The patients in the control group will take Mecobalamin(MeCbl) tablets orally, 1 tablet of a time, 3 times a day, for 4 weeks, and were followed up for 4 weeks. The main outcome measures were the participant neurotoxicity questionnaire (PNQ) and the peripheral neurotoxicity assessment rating (NCI CTCAE V5.0). Secondary outcomes were the quality of life scale (EORTC QLQ-C30) and the measurement of peripheral nerve conduction velocity (NCV). The results will be evaluated at baseline, post-treatment phase and 4-week follow-up. All major analyses will be based on the intention to treat principle. Ethics/dissemination: This protocol was approved by the Medical Ethics Committee of the Cancer Hospital of the University of Chinese Academy of Sciences (Zhejiang Cancer Hospital), on December 7, 2021. The license number is IRB-2021-458. This study will provide clinical efficacy data of different frequency of EA in the treatment of CIPN. The results will help to prove whether EA is an effective therapy for CIPN, and will optimize the frequency of EA for CIPN. The results of this study will be shared with health care professionals, the public and relevant organizations through the publication of manuscripts and conference reports. Trial registration number: ChiCTR2100054458.